Law Enforcement Professional Ethics: An Analysis of Legal Philosophy on Morality and Integrity in Law Enforcement Practice - Hamdi, Fakhri; Hertanto, Yudhi; Karunia, Cindy Armelia; Daniyati, Nuryahyania; Sapsudin, Asep (Sean Institute, 2025)
Professional ethics are a fundamental pillar in maintaining the integrity and public trust in law enforcement agencies. This article aims to analyze the morality and ethical obligations of law enforcement through a legal philosophy approach, particularly through Immanuel Kant's theory of morality, John Rawls's concept of justice, and Lon Fuller's principle of legal internal morality. Using normative-philosophical research methods, this study examines the relationship between moral values, legal norms, and the practice of the law enforcement profession in Indonesia. The results of the analysis show that integrity, honesty, and impartiality are not only demands of the code of ethics, but also a manifestation of the legal morality that underlies the legitimacy of law enforcement actions. This article asserts that without a strong moral foundation, the law loses its value of justice and is incapable of carrying out its social functions. Thus, professional ethics are a primary requirement for creating a fair and humane legal system.